2012
DOI: 10.1186/1746-6148-8-97
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and morphological features of a small bowel leiomyoma in a black crested macaque (Macaca nigra)

Abstract: BackgroundSpontaneous gastrointestinal neoplasms in non-human primates are commonly seen in aged individuals. Due to genetic similarities between human and non-human primates, scientists have shown increasing interest in terms of comparative oncology studies.Case presentationThe present study is related to a case of an intestinal leiomyoma in a black crested macaque (Macaca nigra), kept on captivity by Matecaña Zoo, Pereira City, Colombia. The animal had abdominal distension, anorexia, vomiting, diarrhea and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In macaques, leiomyomas are the most common uterine tumor (termed 'fibroids') and have also been reported in the small intestine of macaques and at the gastroesophageal junction in a chimpanzee. 1,4,9,16 Urinary leiomyoma, like uterine fibroids, contain smooth muscle cells with variable amounts of dense collagenous matrix. 9 Urinary bladder leiomyomas have been reported in humans, dogs, cats, and goats.…”
Section: Discussionmentioning
confidence: 99%
“…In macaques, leiomyomas are the most common uterine tumor (termed 'fibroids') and have also been reported in the small intestine of macaques and at the gastroesophageal junction in a chimpanzee. 1,4,9,16 Urinary leiomyoma, like uterine fibroids, contain smooth muscle cells with variable amounts of dense collagenous matrix. 9 Urinary bladder leiomyomas have been reported in humans, dogs, cats, and goats.…”
Section: Discussionmentioning
confidence: 99%
“…There are no standardized rodent animal models for the study of spontaneous uterine leiomyomas. However, nonhuman primates utilized in breeding colonies and aging studies have shown that spontaneous development of leiomyomas and leiomyosarcomas being the most commonly reported uterine tumors in rhesus macaques [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%